Play While Writing: Breakthroughs for Digital Literacy Activities during the Covid-19 Pandemic - Aswan Aswan (Jurnal Pendidikan Bahasa, 2020)
Covid-19 presence in the world has paralyzed the education system. Indonesia became one of the countries affected by Covid-19. The education system, which is usually conducted face-to-face, is forced to go online to reduce the risk of contracting the Covid-19 outbreak. Literacy activities that are considered important in schools are also affected by Covid-19. Seeing these problems, this study aims to create a literacy learning model that focuses on writing activities. The writing learning model with the play approach is a renewal in online writing activities. The method used in this research is qualitative. The sampling technique used is purposive sampling. The data analysis technique used is an interactive analysis model from Miles and Huberman. Informants in this study amounted to 30 people consisting of students, students, and the public. The Play While Writing Model starts with the conditioning of the class, the provision of relevant material, the instructions for playing, the process of playing while writing, the feedback from the informants, and the closing. The estimated online learning time is approximately one hour and thirty minutes. The results showed that the online writing learning model with a playful approach could attract informants. The writing learning model Playing While Writing makes students active, creative, and eager to express ideas in writing. As a whole, it can be said that the learning model of Playing While Writing can be a breakthrough in digital literacy during the Covid-19 pandemic.